Semiconductor Physical Electronics - Li, Sheng S. (Springer New York : Imprint: Springer, 2006)
Semiconductor Physical Electronics, Second Edition, provides comprehensive coverage of fundamental semiconductor physics that is essential to an understanding of the physical and operational principles of a wide variety of semiconductor electronic and optoelectronic devices. This text presents a unified and balanced treatment of the physics, characterization, and applications of semiconductor materials and devices for physicists and material scientists who need further exposure to semiconductor and photonic devices, and for device engineers who need additional background on the underlying physical principles. This updated and revised second edition reflects advances in semicondutor technologies over the past decade, including many new semiconductor devices that have emerged and entered into the marketplace. It is suitable for graduate students in electrical engineering, materials science, physics, and chemical engineering, and as a general reference for processing and device engineers working in the semicondictor industry. .